Grammatical Errors in English Job Advertisements - Monica, Monica; Hatim, Magdad; Mayasari, Santi (Universitas Islam Negeri Raden Intan Lampung, 2022)
There are many official job advertisement websites provided by companies that can be reached by job seekers. Many of them are available in English. The researcher aimed to identify the types of grammatical errors and the frequencies and percentages of each type of grammatical errors. The research method of this research was qualitative descriptive. The data of the research were taken from fifteen JS document publication job advertisement texts. Seven steps of Creswell data analysis were used in analyzing errors which included: organizing and preparing the data analysis, reading all the data, starting coding all of the data, using the coding process to generate a description of the setting as well as categories for analysis, quantifying the errors, interpreting the description, and drawing a conclusion. It was found that there were 250 errors made by advertisement text writers. Four types oferrors were found in the data.Such errors were 91 items (36.4%) of omission errors, 20 items (8.0%) of addition errors, 138 items (55.2%) of misformation errors, and 1 item (0.4%) of misordering errors.